Porous alumina powder for lithium-ion batteries, battery separator, battery, and electrical equipment

By using porous alumina powder with specific particle size and morphology, the electrolyte wettability of lithium-ion battery polymer separators is improved, and the problem of insufficient performance of existing separators is solved, and more efficient electrolyte diffusion and membrane performance optimization is achieved.

CN119038966BActive Publication Date: 2025-04-25SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411525867.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-04-25
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The polymer separators of existing lithium-ion batteries have insufficient wetting and heat resistance due to material characteristics, which affect the electrochemical performance of the battery.

Method used

Porous alumina powder with specific particle size and morphology is used to improve the electrolyte wetting of polymer separators and form an efficient separator coating.

Benefits of technology

The diffusion rate and diffusion radius of the electrolyte on the diaphragm are improved, the dynamic contact angle is reduced, the adsorption rate of the electrolyte is enhanced, and the thermal shrinkage performance and mechanical strength of the diaphragm are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038966B_ABST
    Figure CN119038966B_ABST
Patent Text Reader

Abstract

The present invention provides a porous alumina powder and battery separator, battery, and electrical equipment for lithium-ion batteries, and relates to the technical field of battery materials. The porous alumina powder includes alumina particles with a quadrangular prism structure, the amount of which is at least not less than 50%, the amount of alumina particles with a spherical structure is no more than 1%, and the amount of alumina particles with a needle-shaped structure and a sheet-like structure is no more than 5%; the ratio of the edge length to the diagonal length of the bottom surface of the alumina particles with a quadrangular prism structure is 1: (0.5~5). The present application also provides a battery separator, battery, and electrical equipment based on the porous alumina. The porous alumina provided in the present application is conducive to optimizing the electrolyte wettability of the polymer separator, so that the electrolyte diffusion radius of the separator is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery materials, and in particular to a porous alumina powder, a battery separator, a battery and an electrical device for lithium-ion batteries. Background Art

[0002] The main structures in the lithium-ion battery system are the negative electrode, the separator and the positive electrode, as well as the electrolyte filled between the negative electrode and the positive electrode. The charging process of the lithium-ion battery is that the lithium ions are deintercalated from the positive electrode material, migrate to the surface of the negative electrode material through the separator and the electrolyte, and are inserted into the crystal structure of the negative electrode material; and the discharge process is: the lithium ions are deintercalated from the crystal structure of the negative electrode material, migrate to the surface of the positive electrode material through the electrolyte and the separator, and are embedded in the crystal structure of the positive electrode material.

[0003] It can be seen that during the charge and discharge process of the battery, the transmission rate of lithium ions in the diaphragm directly affects the charge and discharge efficiency of the battery. The diaphragm in the existing lithium-ion battery system is mainly a polymer diaphragm. Since the polymer diaphragm is made of a high molecular polymer, such as polyolefin, it has poor wettability to aqueous electrolytes and poor heat resistance, so it cannot assist in improving the electrochemical performance of the battery. In order to improve the heat resistance of the polymer diaphragm, those skilled in the art have proposed coating a ceramic coating on the surface of the diaphragm, but the addition will cause the conductivity of the lithium ions of the diaphragm to decrease, and will also affect the wettability of the electrolyte to the diaphragm, thereby affecting the ionic conductivity of the diaphragm. Furthermore, the reason why the polymer diaphragm causes poor wettability of the electrolyte is mainly due to the poor affinity between the base film of the high molecular polymer and the electrolyte. Therefore, the optimization of the wettability of the polymer diaphragm is currently mainly focused on the optimization of the polymer base film, and little attention is paid to the optimization of the wettability of the diaphragm in the ceramic coating. Summary of the invention

[0004] The object of the present invention is to provide a porous alumina powder for lithium ion batteries, wherein the particles of the porous alumina powder are conducive to optimizing the electrolyte wettability of a polymer separator.

[0005] Another object of the present invention is to provide a battery separator.

[0006] Another object of the present invention is to provide a battery.

[0007] Another object of the present invention is to provide an electrical device.

[0008] In a first aspect, the present application provides a porous alumina powder for lithium-ion batteries, wherein the particle size D50 of the porous alumina powder is 0.3-2 μm; the specific surface area of ​​the porous alumina powder is 5-50 m 2 / g; the porous alumina powder comprises alumina particles with a quadrangular prism structure of at least 50%, alumina particles with a spherical structure of at most 1%, and alumina particles with a needle-shaped structure and a flaky structure of at most 5%;

[0009] The ratio of the edge length to the diagonal length of the bottom surface of the alumina particles with a quadrangular prism structure is 1: (0.5~5).

[0010] Furthermore, in some embodiments of the present application, the porous alumina powder includes alumina particles with a quadrangular prism structure, in which the amount of alumina particles is at least not less than 90%, the amount of alumina particles with a spherical structure is no more than 0.5%, and the amount of alumina particles with a needle-shaped structure and a lamellar structure is no more than 2%.

[0011] Furthermore, in some embodiments of the present application, the content of α-alumina in the porous alumina powder is not higher than 50%.

[0012] Furthermore, in some embodiments of the present application, the surface hydroxyl content of the porous alumina powder is 8 / nm 2 Below, and its infrared spectrum at wave number 1600cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 50cm -1 The following infrared peaks.

[0013] Furthermore, in some embodiments of the present application, the surface hydroxyl content of the porous alumina powder is 5 / nm 2 Below, and its infrared spectrum at wave number 1600cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 100cm -1 The following infrared peaks.

[0014] Furthermore, in some embodiments of the present application, each particle in the porous alumina powder includes a plurality of pores, the pore diameter of the pores is 5-50 nm, and the pore volume is 0.01-0.4 cm 3 / g; the specific surface area of ​​the porous alumina powder is 5~50 m 2 / g.

[0015] Furthermore, in some embodiments of the present application, the pore diameter is 8-20 nm, and the pore volume is 0.05-0.2 cm 3 / g; the specific surface area of ​​the porous alumina powder is 6~20m 2 / g.

[0016] Furthermore, in some embodiments of the present application, the particles in the porous alumina powder are at least one of the θ phase, δ phase, and γ phase, or at least one of the η phase, κ phase, χ phase, and ρ phase.

[0017] Furthermore, in some embodiments of the present application, the porous alumina powder is directly prepared without compounding multiple porous alumina powders.

[0018] In a second aspect, the present application also provides a battery separator, which comprises the porous alumina described in the first aspect.

[0019] Further, in some embodiments of the present application, the battery separator is a battery separator, and the battery separator comprises a substrate and a coating formed on at least one side of the substrate, wherein the porous alumina is distributed in the coating;

[0020] The liquid absorption performance of the battery separator is not less than 0.6 mL / g.

[0021] In a third aspect, the present application further provides a battery, comprising the battery separator described in the second aspect.

[0022] In a fourth aspect, the present application also provides an electrical device, comprising the battery described in the third aspect.

[0023] The embodiments of the present application provide a porous alumina, an electronic component, a battery, and an electrical device. The porous alumina has very few needle-shaped, flaky, and spherical alumina particles, and is mainly composed of alumina particles with a tetrahedral structure. The surface convex points of the coating formed by the alumina are few and the flatness is high. The electrolyte wettability of the diaphragm is optimized very significantly, which not only makes the diffusion rate of the electrolyte on the diaphragm high, but also makes the diffusion radius larger, the dynamic contact angle is significantly reduced, and the electrolyte adsorption rate is also high. Moreover, the specific surface area of ​​the porous alumina powder provided by the present application is lower than that of the alumina powder with a high specific surface area, but higher than that of the conventional α-alumina powder, and its stability is better and the adsorption of water is weaker, which avoids the defects of electrolyte consumption and ion transmission channel blockage caused by the difficulty in reducing the water content in the alumina powder or the increase in activity and decrease in stability due to water absorption during use.

[0024] The porous alumina powder provided in the present application also has both stability and dispersibility, and when applied to diaphragm coatings, it is beneficial to improve the thermal shrinkage performance and mechanical strength of the diaphragm, and it can provide more ion transmission channels for ion conduction, which is beneficial to the optimization of the performance of the battery diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is an electron microscope image of the porous alumina prepared in Example 1 of the present application.

[0026] Figure 2 This is the infrared spectrum of the porous alumina provided in Example 1 of the present application. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The polymer separator mainly composed of high molecular polymers in lithium-ion batteries is the main evolution and research and development direction of lithium-ion batteries. However, the wettability of high molecular polymers to aqueous electrolytes is poor, which is not conducive to the conduction of ions in the separator, affecting battery performance and is one of the main reasons for the influence of the separator on the electrical performance of the battery. In this regard, since ceramic coatings are usually hydrophilic, especially alumina coatings, and high molecular polymers are the main reason affecting the wettability of the separator, the current research on improving the wettability of the separator is mainly focused on the polymer base film of the separator, while the influence of ceramic coatings on the wettability of the separator is less studied, or mainly focused on the modification of inorganic particles of ceramic coatings. However, the hydrophilic modification of modified inorganic particles, such as alumina particles, easily leads to an increase in their water content, poor dispersibility, and reduced stability, especially porous alumina particles. Alumina is often used in the coating of battery separators, electrode material coatings, and other battery structural parts in contact with electrolytes. One of its main advantages is good chemical stability. Therefore, the applicant aims to provide a porous alumina particle with improved and optimized wettability to the separator without modifying the alumina.

[0029] To this end, the applicant proposed an alumina powder in the present application, in which the alumina particles are particles with a porous structure, and the morphology of the particles is mainly quadrangular prism-shaped, and there are fewer or no alumina particles with other morphologies. That is, the applicant provided a porous alumina particle with a specific particle morphology within a specific particle size range (D50 is 0.3~2μm), and unexpectedly found that the diaphragm coating formed by alumina based on this feature has a particularly obvious improvement in wettability for diaphragms with polymer substrates as base membranes, which provides a prerequisite for optimizing the electrical properties of the diaphragm.

[0030] The applicant believes that the reason may be that, based on the morphology and particle size of the alumina particles, when forming a coating, the stacking form of the alumina particles may be more inclined to form a stacking form similar to: "short-range order, long-range disorder", which is manifested in the large stacking angle of the porous alumina powder; and the relatively uniform width of the gaps between the particles, and the mesopores on the particles form a network of straight capillary channels + nanoscale capillary tunnels within a specific range (mesopores on the particle surface), so that the electrolyte can quickly infiltrate, diffuse and divert, thereby promoting the infiltration and diffusion of the electrolyte on the surface of the diaphragm.

[0031] The inventors found that when alumina is used as an inorganic particle in a battery separator, the stacking form of the alumina particles has a significant effect on the layer structure formed by the stacking of the alumina particles. However, since the particle size of alumina powder is usually nanometer or micrometer, it is impossible to subjectively control the stacking form of the alumina. The inventors found that the stacking form of the alumina particles can be controlled to a certain extent by controlling the morphology of the alumina particles. The porous alumina powder proposed in the present application has a layer structure in which the stacking form of the porous alumina particles tends to form a stacking form similar to: "short-range order, long-range disorder". When it is applied to diaphragm coatings, it exhibits a coating with high surface flatness, few or even no protrusions, especially thin coatings (coatings with a thickness of less than 3μm). The improvement of the coating surface flatness and surface protrusions is beneficial to reducing the safety and thermal shrinkage of the diaphragm, and is also beneficial to the optimization of its mechanical strength. On the basis of thermal shrinkage, mechanical strength and stability, the optimization of the porous structure and stacking form of the particles is beneficial to the absorption and storage of electrolyte and the increase of ion transmission channels on the basis of improving the wettability of the diaphragm.

[0032] The solutions provided in this application are as follows:

[0033] The particle size D50 of the porous alumina powder is 0.3~2μm; the porous alumina powder includes alumina particles with a quadrangular prism structure, the amount of which is at least not less than 50%, the amount of alumina particles with a spherical structure is no more than 1%, and the amount of alumina particles with a needle-shaped structure and a lamellar structure is no more than 5%; the ratio of the edge length of the alumina particles with a quadrangular prism structure to the diagonal length of the bottom surface is 1: (0.5~5).

[0034] In the present application, alumina particles with a tetrahedral prism structure refer to particles whose apparent morphology (ignoring the surface gaps formed by the porous structure on the surface) is a prism structure surrounded by six rectangles or parallelograms (including two end faces and four side faces). The two end faces of the particle are rectangles or parallelograms, and the four side faces are perpendicular to the two end faces. The edge length is the length of the edge on the side of the alumina particle that is perpendicular to the end face; the bottom face is the diagonal length of the longer of the two diagonals on the end face.

[0035] Preferably, the ratio of the edge length to the diagonal length of the bottom surface of the aluminum oxide particles having a quadrangular prism structure is 1:(1-3).

[0036] In the present application, alumina particles with a spherical structure refer to particles with a spherical or quasi-spherical shape, such as alumina particles with a sphericity of not less than 95% or higher. Alumina particles with a needle-shaped structure refer to alumina particles with a conical, quasi-conical, rod-shaped, strip-shaped or similar shape; alumina particles with a sheet-shaped structure refer to alumina particles with a sheet-shaped or nearly sheet-shaped or layered structure composed of multiple sheets; in the single-layer structure of the sheet-shaped or layered structure constituting the alumina particles, the ratio of the edge length to the side length of the end face is not less than 10, or even not less than 20, which is obviously manifested as a sheet-shaped structure in which the edge height is much lower than the side length of the end face.

[0037] When the alumina particles provided in the present application are in a stacked state, the stacking angle of repose in the free stacking state is 38°~45°, which is significantly higher than the stacking angle of repose of spherical or quasi-spherical alumina particles with the same particle size (usually <15°). The applicant speculates that the possible reason is that a partial "short-range order, long-range disorder" stacking form is formed during the stacking process, which greatly increases the contact area between particles, increases friction, and thus increases the stacking angle of repose of the powder. It should be noted that the "short-range order, long-range disorder" stacking form described in the present application is not a short-range order in the strict sense, but refers to the tendency of adjacent particles on the same plane to be arranged in contact with each other in a parallel face-to-face contact manner, rather than a point-to-point contact manner.

[0038] The porous alumina particles with a tetrahedral structure provided in the present application tend to form a "short-range order and long-range disorder" stacking form when applied to the diaphragm coating. The contact area between adjacent porous alumina particles and the contact area between the alumina particles and the substrate are increased, and it is not easy to slip, which is beneficial to improve the thermal shrinkage, mechanical strength (puncture strength) and other properties of the diaphragm. The surface flatness of the coating formed by it is high; in addition, although the porous alumina particles provided in the present application have a high angle of repose, they have good dispersion performance, are not easy to agglomerate, and there are almost no convex points on the coating formed by them. The possible reason may be that although the alumina particles provided in the present application are porous particles, their specific surface area is not high, the hydroxyl content contained on the surface is also extremely low, and the affinity with water is low. Therefore, the probability of agglomeration between particles due to water molecules attached to the surface is low, and the porous structure on its surface reduces the actual area of ​​contact between adjacent particles, so that although it is not easy to slip, the actual contact area between the faces is much lower than that of non-porous particles, so it is not suitable for agglomeration. At the same time, since the alumina particles provided in the present application are porous alumina particles, the mesopores on the alumina can provide channels for ion conduction, increase the ion conductivity, and there may be a special nano-capillary tunnel effect, which has an optimization effect on the absorption and diffusion of the electrolyte. In addition, it may form a two-level capillary channel with the gap between the particles, which enhances the adsorption and diffusion of the electrolyte, and is conducive to the optimization of the amount of liquid absorption and the improvement of wettability; and due to its "long-range disordered" stacking form, the coating formed by it is easy to show isotropy, and under the same tensile conditions, the optimization of the longitudinal tensile strength and the transverse tensile strength of the diaphragm is close to similar. In addition, due to its quadrangular prism structure and "short-range ordered" stacking structure, it is not easy to form overlapping stacking for thin coatings, which reduces the specific surface loss of alumina particles caused by overlapping, and the air permeability of the diaphragm used for it decreases significantly. Moreover, the strength of the alumina particles with a quadrangular prism structure is more advantageous than that of the flaky and needle-shaped alumina particles, and it can reduce the sharp protrusions of the formed coating and reduce the damage to the substrate and coating equipment.

[0039] In addition, the particles in the alumina powder provided in the present application are porous particles, each of which has a number of nanopores, so that its specific surface area is relatively increased, the ion transmission channel is increased, and the decrease in the permeability value of the diaphragm caused by the coating setting is reduced.

[0040] Preferably, the porous alumina powder includes a tetrahedral prism structure of alumina particles in an amount of at least 90%, and the amount of spherical alumina particles is no more than 0.5%, and the amount of needle-shaped and flaky alumina particles is no more than 2%. More preferably, the porous alumina powder includes a tetrahedral prism structure of alumina particles in an amount of at least 99%, and even infinitely approaches 100%.

[0041] The alumina particles in the porous alumina powder provided in the present application have good morphological consistency, which is more conducive to forming a "short-range ordered, long-range disordered" stacking form, and is more conducive to reducing the internal stress of the coating, improving the flatness and mechanical strength of the coating, and is conducive to reducing the coating thickness of the diaphragm under the condition of the same coating performance.

[0042] Preferably, the porous alumina powder provided in the present application has a narrow particle size distribution, and the value of (D90-D10) / D50 is not higher than 3, or even not higher than 2. When it is applied to the diaphragm coating, the formed diaphragm coating has higher flatness and better uniformity; at the same time, it can also shorten the ion transmission path, improve ion conductivity, and optimize battery performance. More preferably, the porous alumina particles in the porous alumina powder provided in the present application are mainly alumina single crystals, which have a narrow particle size distribution and good morphology uniformity. When applied to the diaphragm coating, the coating uniformity and flatness are better, which is conducive to further reducing the coating thickness of the diaphragm, reducing the diaphragm density, and improving the volume energy density of the battery under the same coating performance.

[0043] Preferably, the D50 of the porous alumina powder provided in the present application is 0.4 μm to 1 μm, more preferably 0.5 μm to 0.6 μm. More preferably, the ratio between the modal diameter and the D50 particle size of the porous alumina powder provided in the present application is 0.9 to 1.1; the particle size distribution of the porous alumina powder provided in the present application is a normal distribution or infinitely close to a normal distribution.

[0044] It should be noted that the D50 particle size in this application refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D90 refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%; D10 refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 10%; the mode diameter is the particle size corresponding to the maximum frequency density of the particle size distribution.

[0045] It should be noted that in order to ensure the chemical stability of aluminum oxide, the specific surface area of ​​aluminum oxide particles used in battery separators in contact with the electrolyte should not be too high, and the activity should not be too good, because aluminum oxide particles with a high specific surface area are prone to difficulty in removing water molecules, resulting in the introduction of water into the battery, which in turn affects the battery's service life, battery performance and safety. Alumina with higher activity is prone to react with components in the electrolyte, leading to problems such as electrolyte consumption and ion transmission channel blockage.

[0046] The porous alumina powder provided in the present application has a plurality of pores on its particles, the pore diameter of which is 5 to 50 nm, preferably 8 to 20 nm; the specific surface area is 5 to 50 m 2 / g, more preferably 6 to 40 m2 / g, more preferably 6 to 20 m 2 / g.

[0047] The alumina particles in the porous alumina powder provided in the present application are mainly of a tetrahedral structure, and in fact, the alumina particles are mainly single crystals of alumina, and the pores are formed on the surface and inside of the single crystal alumina particles, and the crystals have good stability and low specific surface area, which is relatively high compared to the specific surface area (such as 150m 2 / g or more), it is easier to form aluminum oxide powder with lower water content during the preparation process, and the water content stability in the aluminum oxide powder during storage is also better, and it is not easy to have defects such as agglomeration and adhesion. However, aluminum oxide powders with ultra-high specific surface area, especially nano-scale or submicron-scale aluminum oxide powders, often have defects such as difficult water removal and fast agglomeration due to their good hydrophilicity and high specific surface area. However, the specific surface area of ​​the porous aluminum oxide powder provided in the present application is not low, which can increase the specific surface area of ​​aluminum oxide and increase the space for absorbing and storing electrolyte, so that its absorption of electrolyte and ion transmission channels are increased. At the same time, due to its low specific surface area, while increasing the absorption of electrolyte and ion transmission channels, it can also have both water absorption and dispersibility in slurry.

[0048] The pore volume of the porous alumina powder provided in this application is 0.01-0.4cm 3 / g, preferably 0.05-0.2cm 3 / g.

[0049] It should also be noted here that long-term contact between alumina powder and water molecules will cause a slow hydration reaction to occur, generating high-viscosity, highly active hydrated alumina. Therefore, a low and stable water content in alumina powder is critical for its application in batteries.

[0050] The porous alumina powder provided in this application has a low water content. The surface hydroxyl content is found to be 8 / nm. 2 Below, and its infrared spectrum at wave number 1600cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 50cm -1The following infrared peaks show that the water content can be almost as low as invisible. In addition, the inventors also placed the prepared porous alumina powder in an air environment for 48 hours and then tested the water content therein, and found that the porous alumina powder was stable below 0.3%. It can be seen that the porous alumina powder is also relatively stable and will not quickly absorb moisture in the air, causing it to agglomerate or agglomerate. The reason may be that the porous alumina particles in the porous alumina powder provided in the present application are mainly single crystals of alumina. When forming alumina crystals and pore structures, the aluminum atoms in the crystals are not exposed in large quantities, making it difficult to combine with the hydroxyl groups in the water molecules, so that it does not show obvious water absorption performance, thereby improving its stability in a water vapor environment. The applicant found that although there are still very small amounts of hydroxyl groups on the surface of the porous alumina powder after detection, no vibration peak of hydroxyl groups appears in the infrared spectrum. At the same time, the stability of the porous alumina in water or water vapor and its dispersibility in slurry are unexpectedly excellent. Its viscosity and stability in water or aqueous solutions are unexpectedly optimized, which is conducive to the application of porous alumina powder in battery components that are in contact with the electrolyte, such as isolation membranes.

[0051] Preferably, the surface hydroxyl content of the porous alumina powder is 5 / nm 2 Below, and its infrared spectrum at wave number 1600cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 100cm -1 More preferably, the surface hydroxyl content of the porous alumina powder is 3 to 5 per nm. 2 .

[0052] In the porous alumina powder provided in the present application, the particles in the porous alumina powder are at least one of the θ phase, δ phase, γ phase, α phase or at least one of the η phase, κ phase, χ phase, ρ phase.

[0053] It should be noted that when the porous alumina powder includes γ-phase alumina, it includes at least one of δ-phase, η-phase, κ-phase, χ-phase, and ρ-phase alumina in addition to the γ-phase alumina; when the porous alumina powder includes α-phase alumina, the content of α-alumina in the porous alumina powder is not higher than 50%, and more preferably not higher than 20%.

[0054] Furthermore, in order to improve the porous alumina provided in the present application, the content of γ-alumina in the porous alumina provided in the present application is preferably lower, such as lower than 10% or lower than 8%, so as to improve the chemical stability of the porous alumina and reduce the activity.

[0055] The total content of metal elements such as iron, cobalt, chromium, zinc and nickel in the porous alumina provided by the present application can reach less than 500ppm. The reason may be that the porous alumina particles provided by the present application are mainly single crystal particles, and the integrity of the crystal particles is relatively high; and in the preparation process, the porous formation is not formed by granulation, but by the escape of water molecules in the crystal particles and the displacement of atoms during the crystal phase change process; it makes it difficult for metal elements to embed into the porous alumina particles and attach to the surface of the single crystal particles, making it easier for other metal ions in ionic state to remain in the reaction system and be removed by cleaning or demagnetization and impurity removal.

[0056] It should be noted that the porous alumina powder provided in the present application is directly prepared from raw materials without compounding multiple porous alumina powders. That is, the porous alumina particles in the porous alumina powder provided in the present application are mainly quadrangular prism particles, and there are no or very few alumina particles with spherical / quasi-spherical, needle-shaped, sheet-shaped, etc. morphologies, and the porous alumina particles have a narrow particle size distribution. The powder is not formed by screening, grading, or compounding, but the morphology of the product after direct preparation is such.

[0057] In this regard, in order for those skilled in the art to better understand and implement the present application, a preparation method for the above-mentioned porous alumina powder is also provided below.

[0058] Step (1): providing aluminum hydroxide, alcohol, inorganic acid and pure water, mixing them, stirring and reacting them at a temperature of 60° C. to 80° C. for 30 min to 60 min to obtain a precursor solution; controlling the stirring speed to be 30 Hz to 50 Hz;

[0059] Step (2): Mix the precursor solution with the organic acid and pure water, raise the temperature to 60°C~80°C, stir and react for 1h-3h; then raise the temperature to 150°C~200°C, keep the temperature and react for 4h~48h to obtain an intermediate; control the reaction pressure to 1.4~3.7MPa;

[0060] Step (3): washing, demagnetizing, drying, calcining at 600°C to 1200°C for 0.5 to 5 hours, and jet milling to obtain porous alumina powder.

[0061] Wherein, a small amount of barrier agent that can be decomposed into gas at a relatively low temperature is added in step (3), and the decomposition temperature of the barrier agent is not higher than 450°C, more preferably not lower than 50°C and not higher than 100°C. Exemplarily, the barrier agent can be ammonium bicarbonate, ammonium carbonate, ammonium nitrate, preferably ammonium carbonate; the amount of the barrier agent is 0.01% to 0.1% by mass of the dried intermediate powder obtained in step (3). The barrier agent can be added in the drying stage or in the calcining stage. When it is added in the calcining stage, it can also reduce the adhesion of particles to the wall of the container used for calcining during the calcining process.

[0062] In addition, the inventors have also found that in order to control the consistency of the morphology of the porous alumina powder, it has a significant relationship with the morphology and purity of the intermediate before calcination, the content of crystal water in the intermediate and the temperature control of the calcination process; the intermediate before calcination also needs to be controlled to be an intermediate with a main quadrangular prism structure and there are no or almost no spherical or quasi-spherical particles therein; and the intermediate before calcination is preferably a single crystal particle with a narrow particle size distribution and good morphology consistency; and the inventors unexpectedly found that the content of crystal water in the intermediate is not more than 35% by mass fraction, preferably the content of crystal water is not less than 5%, and preferably the content of crystal water is not less than 16%. Within this range, the pore volume, pore size and hydroxyl content of the porous alumina particles formed by the intermediate can be controlled within the required range, and the porous alumina particles also show a wave number of 1600cm in the infrared spectrum. -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 50cm -1 The following infrared peaks may be caused by controlling the content of crystal water in the intermediate, the morphology of the intermediate and the calcination process during the preparation process, so that the aluminum atoms and oxygen atoms in the porous alumina crystals are more likely to be exposed when they move during the crystal phase change process, while the aluminum atoms are less exposed, so that the obtained alumina particles can remain stable even in an environment containing water molecules. It should be noted that the "wave number 1600cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 50cm -1 The "infrared peak below" refers to a peak that appears obvious and has a transmittance below 98%.

[0063] Wherein, in step (2), the reaction system obtained in step (1) is added to step (2) as a whole, and alcohol and inorganic acid (strong acid) are introduced into the reaction system in step (1), and form a pH buffer with the organic acid (weak acid) added in step (2), so that during the reaction, the reaction system is maintained at a significant acidity, and at the same time, the hydrogen ion content does not change significantly with the occurrence of the reaction, which promotes the formation of intermediates and the consistency of the intermediates is good. In addition, the addition of alcohol introduces a certain amount of alkyl into the system. The presence of alcohol may replace the hydroxyl group and thus affect the deprotonation process, which can slow down the reaction rate and the degree of completion of the reaction, promote the dissolution of the generated aluminum hydroxide, further promote the transport and transfer of metal oxygen ions, and regulate the nucleation and growth of the intermediates. The intermediates formed by the above means have better crystal particle size and grain consistency, which may be due to the fact that after the reaction rate is reduced, the dissolved aluminum hydroxide is more inclined to heterogeneously nucleate and grow on the undissolved aluminum hydroxide, and the aluminum nitrate in the precursor solution provides more metal aluminum ions, increasing the supersaturation of the system and increasing the nucleation driving force. In addition, the intermediate obtained by the preparation method provided above has a high crystal water content, and the possible reason is that the complex formed by aluminum ions and citrate during the reaction inhibits the crystallization process, making the crystallization incomplete. In addition, the entire reaction is mainly the dissolution, transportation and dehydration crystallization of aluminum hydroxide. During the crystallization process, the water-free aluminum complex may compete with aluminum hydroxide for hydroxyl groups and occupy special lattice sites, thereby inducing a large amount of lattice distortion and oxygen vacancies and aluminum gaps, resulting in incomplete crystallization and reduced dehydration effect and increased crystal water content, thereby forming an intermediate with a high crystal water content. Based on these lattice defects and crystal water being released in subsequent calcination, the crystal structure collapses to form a porous structure; in addition, the anions in the further reaction system are adsorbed by cations during the crystallization process, thereby promoting or inhibiting the growth of the grains along a specific direction or crystal plane, thereby causing the anisotropic growth of the crystals, which may be the reason why the alumina particles exhibit a specific morphology.

[0064] In this preparation method, the mass ratio of aluminum hydroxide, alcohol, inorganic acid and pure water is 1:1:0.1~0.3:1~3; in step (2), the mass ratio of precursor solution to organic acid and pure water is 1:0.12~0.2:0.2~0.4; the mass ratio of inorganic acid to organic acid is controlled to be 0.16~0.5; the mass ratio of alcohol to organic acid is 1.2~2.0.

[0065] Among them, the alcohol can be one or more common alcohol solvents such as ethanol, propanol, n-butanol, isobutanol, pentanol, isopentanol, etc.; the inorganic acid can be one or more inorganic strong acids such as nitric acid, sulfuric acid, hydrochloric acid, etc.; the organic acid can be one or more organic weak acids such as acetic acid, oxalic acid, citric acid, etc.

[0066] Preferably, in step (3), the temperature curve of the calcination process is preferably: rapidly heating to at least 250°C at a heating rate of not less than 5°C / s, reducing the heating rate (the heating rate is not higher than 1°C / s) and then heating to the holding temperature, and then sintering at the holding temperature for 0.5 to 5 hours to obtain a product, so as to promote the maintenance of the single crystal morphology of the porous alumina particles and the control of the pore size and pore volume.

[0067] The drying method is preferably infrared microwave drying. When infrared microwave drying is used, the intermediate powder after drying does not need to be broken up or crushed, and can directly enter the calcination process, which saves costs and improves the morphological integrity of the product. In addition, in order to achieve a good dispersion effect, when infrared microwave drying is used, the slurry after demagnetization is first filtered into a filter cake with a free water content of not less than 60%, and then broken into small pieces of filter cake, and then heated to a temperature of not less than 150°C by infrared light irradiation, and after 8-15 minutes of treatment, the temperature is lowered to 80-100°C, and microwave heating is used for 3-10 minutes, and then the temperature is raised to above 150°C by microwave heating until the small filter cake automatically explodes into powder.

[0068] The intermediate powder formed by segmented drying using an infrared microwave drying process has a low water content, which can reach a water content (free water) of no more than 0.2%. In this process, the appearance of the particles is not damaged by grinding or ball milling, and the integrity is better. Moreover, since there is no high-temperature spraying process and automatic explosion into powder, the crystal particles in the obtained powder are less agglomerated and the single crystal dispersion of the product is better.

[0069] After the intermediate is obtained and before demagnetization, the pH value of the intermediate slurry is adjusted to 7-8.5, preferably 7.5-8.0, with an organic acid, and then demagnetization is performed, and the intermediate slurry is dried by a drying method. The drying method can be spray drying or infrared microwave drying. When spray drying is adopted, a disintegration process is also included after spray drying and before calcination, and the dried particles are dispersed into 0.2-5 μm by air jet milling or grinding.

[0070] The drying method is also preferably infrared microwave drying. Similarly, when infrared microwave drying is used, the dried intermediate powder does not need to be broken up or crushed, and can directly enter the calcination process, saving costs and improving the morphological integrity of the product. In addition, in order to achieve a good dispersion effect, when infrared microwave drying is used, the slurry after demagnetization is first filtered into a filter cake with a free water content of not less than 60%, and then broken into small pieces of filter cake, and then heated to a temperature of not less than 150°C by infrared light irradiation, after 8 to 15 minutes of treatment, the temperature is then reduced to 80 to 100°C, and microwave heating is used for 3 to 10 minutes, and then microwave heating is used to raise the temperature to above 150°C until the small filter cake automatically explodes into powder. Similarly, the intermediate powder formed by segmented drying using an infrared microwave drying process has a low moisture content, which can reach a moisture content (free water) of no more than 0.2%. In addition, during this process, the appearance of the particles is not damaged by grinding or ball milling, and the integrity is better. Moreover, since there is no high-temperature spraying process and automatic explosion into powder, the crystal particles in the obtained powder are less likely to agglomerate, and the single crystal dispersion of the product is better.

[0071] The intermediate prepared thereby also has a crystalline water content of no more than 35% by mass fraction, preferably a crystalline water content of no less than 5%, preferably a crystalline water content of no less than 16%, and a mainly quadrangular prism-shaped morphology, with a particle size mainly distributed in the range of 0.2 to 5 μm.

[0072] Similarly, in step (2), a small amount of a barrier agent that can be decomposed into gas at a relatively low temperature is added, and the decomposition temperature of the barrier agent is not higher than 450°C, more preferably not lower than 50°C and not higher than 100°C. Exemplarily, the barrier agent can be ammonium bicarbonate, ammonium carbonate, ammonium nitrate, preferably ammonium carbonate; the amount of the barrier agent is 0.01% to 0.1% by mass of the dried intermediate powder obtained in step (2). The barrier agent can be added in the drying stage or in the calcination stage. When it is added in the calcination stage, it can also reduce the adhesion of particles to the wall of the container used for calcination during the calcination process. The temperature curve of the calcination process is preferably: rapidly heating to at least 250°C at a heating rate of not less than 5°C / min, reducing the heating rate (heating rate is not higher than 1°C / min) and then heating to the holding temperature, and then sintering for 0.5h to 5h to obtain a product, so as to promote the single crystal morphology of the porous alumina particles to be maintained, and the pore size and pore volume to be controlled.

[0073] In this preparation method, the inventors found that directly adjusting the acidity of the slurry after the reaction can promote the consistency of the crystal structure and particle size and the pore size distribution of the product. The reason may be that directly adjusting the acidity after the reaction can dissolve the aluminum hydroxide, making the intermediate obtained more pure, and causing a large number of defects to appear on the intermediate, providing biased guidance for the subsequent formation and development of pores.

[0074] In a second aspect, the present application also provides a battery separator, which comprises the porous alumina described in the first aspect.

[0075] Among them, the battery separator can be a battery separator, which includes a substrate and a coating formed on at least one side of the substrate, and the porous alumina is distributed in the coating; the liquid absorption performance of the battery separator is not less than 0.6mL / g.

[0076] In a third aspect, the present application further provides a battery, comprising the battery separator described in the second aspect.

[0077] In a fourth aspect, the present application further provides an electric device, comprising the battery described in the third aspect. The electric device may be an electric vehicle, an aircraft, an aircraft, a mobile phone, a tablet computer, a handheld game console, a portable digital device (such as a digital camera), a smart home, a smart wearable (such as a smart bracelet, a smart watch, smart glasses), or any other electric device that can use a lithium-ion solid-state battery.

[0078] In order to facilitate those skilled in the art to understand the innovation of the present application, some preferred embodiments are provided below in conjunction with the accompanying drawings to illustrate the above technical solution.

[0079] Example 1

[0080] This embodiment provides a method for preparing porous alumina powder, comprising the following steps:

[0081] Aluminum hydroxide, n-butanol, nitric acid, and pure water were added to the reaction vessel in a mass ratio of 1:1:0.2:2, the temperature was controlled at 70°C, the stirring speed was controlled at 45Hz, and the reaction was carried out for 30 minutes. Aluminum nitrate, citric acid, and pure water were added to the reaction vessel in a mass ratio of 0.2:0.6:1 according to the aluminum hydroxide, and the filling amount was 60%. The kettle temperature was controlled at 70°C, the stirring speed was controlled at 45Hz, and the reaction was carried out for 2 hours. The heating rate was 5°C / min, the temperature was raised to 150°C, and the temperature was kept for 8 hours; the pressure was 2.12MPa, and a slurry was obtained;

[0082] The slurry is washed with pure water and filtered to obtain an intermediate; the intermediate is dispersed with pure water to form a slurry, demagnetized, and spray-dried at 200-220°C to obtain spray particles; the spray particles are jet-milled to obtain intermediate particles with a particle size mainly distributed in the range of 0.2-5 μm;

[0083] 0.01% ammonium carbonate was added to the intermediate particles by mass fraction, mixed evenly, and then heated to 1100° C. at a heating rate of 5° C. / min and kept warm for 2 h to obtain porous alumina powder.

[0084] Example 2

[0085] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the mass ratio of aluminum nitrate, citric acid, and pure water according to aluminum hydroxide in this embodiment is 0.15:0.45:1; the pressure in the reaction container is controlled to be 2.21 MPa, and the remaining preparation steps are the same as in Example 1 to obtain porous alumina powder.

[0086] Example 3

[0087] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the mass ratio of aluminum nitrate, citric acid, and pure water according to aluminum hydroxide in this embodiment is 0.12:0.36:1; the pressure in the reaction container is controlled to be 2.25 MPa, and the remaining preparation steps are the same as in Example 1 to obtain porous alumina powder.

[0088] Example 4

[0089] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the mass ratio of aluminum nitrate, citric acid, and pure water to aluminum hydroxide in this embodiment is 0.1:0.3:1; the pressure in the reaction container is controlled to be 2.35 MPa, and the remaining preparation steps are the same as in Example 1 to obtain porous alumina powder.

[0090] Example 5

[0091] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the mass ratio of aluminum nitrate, citric acid, and pure water according to aluminum hydroxide in this embodiment is 0.05:0.15:1; the pressure in the reaction container is controlled to be 2.42 MPa, and the remaining preparation steps are the same as in Example 1 to obtain porous alumina powder.

[0092] Example 6

[0093] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the temperature is raised to 180° C. and kept warm for 8 hours. The pressure in the reaction container is controlled to be 3.50 MPa. The remaining preparation steps are the same as those in Example 1 to obtain porous alumina powder.

[0094] Example 7

[0095] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the pressure in the reaction container is controlled to be 1.50 MPa according to the mass ratio of aluminum hydroxide, n-butanol, nitric acid and pure water of 1:0.2:0.2:2.8, and the remaining preparation steps are the same as those of Example 1 to obtain porous alumina powder.

[0096] Example 8

[0097] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, after demagnetization, the slurry is filtered to form a filter cake, and the solid content in the filter cake is not less than 65%; the filter cake is broken into small pieces of filter cake with a diameter of no more than 3 cm, and then the temperature of the small pieces of filter cake is raised to 80°C by infrared light. The infrared is fully turned on during the drying process, and the infrared temperature is about 150°C. After drying for 10 minutes, the temperature of the small pieces of filter cake is raised to 100°C by infrared light, so that the moisture inside the filter cake gradually begins to evaporate. After drying for 7 minutes; the temperature of the small pieces of filter cake is raised to 150°C by microwave, so that the moisture inside and outside the material will evaporate to ≤0.2% and automatically explode to present a powder state, and intermediate particles with a particle size mainly distributed in the range of 0.2~5μm are obtained. The remaining preparation steps are the same as in Example 1 to obtain porous alumina powder.

[0098] Comparative Example 1

[0099] Compared with Example 1, in this comparative example, aluminum hydroxide, n-butanol, nitric acid, and pure water are put into a reactor in a mass ratio of 1:1:0.1:2, the temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 30min. Aluminum nitrate, citric acid, and pure water are put into a reactor in a mass ratio of 0.05:0.6:1 according to aluminum hydroxide, and the filling amount is 60%. The kettle temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 2h. The heating rate is 5°C / min, the temperature is raised to 150°C, and the temperature is kept for 8h. The pressure is 2.33MPa to obtain a slurry. The remaining steps are the same as in Example 1 to obtain a comparative sample.

[0100] Comparative Example 2

[0101] Compared with Example 1, in this comparative example, aluminum hydroxide, n-butanol, nitric acid, and pure water are put into a reactor in a mass ratio of 1:1:0.05:2, the temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 30min. Aluminum nitrate, citric acid, and pure water are put into a reactor in a mass ratio of 0.05:0.6:1 according to aluminum hydroxide, and the filling amount is 60%. The kettle temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 2h. The heating rate is 5°C / min, the temperature is raised to 150°C, and the temperature is kept for 8h. The pressure is 2.23MPa to obtain a slurry. The remaining steps are the same as in Example 1 to obtain a comparative sample.

[0102] Comparative Example 3

[0103] Compared with Example 1, in this comparative example, aluminum hydroxide, n-butanol, nitric acid, and pure water are put into a reactor in a mass ratio of 1:1:0.2:3, the temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, the reaction is 30min, and the filling amount is 60%. The kettle temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 2h. The heating rate is 5°C / min, the temperature is raised to 150°C, and the temperature is kept for 8h. The pressure is 2.10MPa to obtain a slurry. The remaining steps are the same as in Example 1 to obtain a comparative sample.

[0104] Comparative Example 4

[0105] Compared with Example 1, ammonium carbonate was not added during the calcination process in this comparative example, and the remaining steps were the same as those in Example 1 to obtain a comparative sample.

[0106] Comparative Example 5

[0107] Compared with Example 1, aluminum hydroxide, n-butanol, nitric acid, and pure water are put into the reaction vessel in a mass ratio of 1:1:0.2:2, the temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 30min. Aluminum nitrate, nitric acid, and pure water are put into the reaction vessel in a mass ratio of 0.1:0.6:1 according to the mass ratio of aluminum hydroxide, and the filling amount is 60%. The kettle temperature is controlled at 70°C, the stirring speed is controlled at 45Hz, and the reaction is carried out for 2h. The heating rate is 5°C / min, the temperature is raised to 150°C, and the temperature is kept for 8h; the pressure is 2.12MPa, and a slurry is obtained. The remaining steps are the same as in Example 1 to obtain a comparative sample.

[0108] test

[0109] 1. Particle size test

[0110] The test was carried out using a Mastersizer 3000 laser particle size analyzer.

[0111] 2. Pore volume and specific surface area

[0112] The test was carried out using Micromeritics physical adsorption instrument 3030.

[0113] 3. Infrared spectroscopy

[0114] A Nicolet™ is50 Fourier transform infrared spectrometer was used.

[0115] 4. Surface hydroxyl content

[0116] The test was carried out using the NaOH titration method.

[0117] 5. Impurity content

[0118] The test was performed using a Thermo Scientific ICP inductively coupled plasma analyzer.

[0119] 6. Angle of repose

[0120] The test was carried out using an Aode-307 angle of repose tester.

[0121] 7. Particle ratio

[0122] An electron scanning electron microscope is used to take a scanning electron microscope image of the product, and the number of particles N1 and the number of particles with a quadrangular prism structure N2 on the scanning electron microscope image are counted. The proportion of particles with a quadrangular prism structure is calculated by the calculation method of N2 / N1×100%.

[0123] 8. Electrolyte diffusion radius

[0124] On a concentric circle plane, place a diaphragm coated with different alumina (disc with a radius of 60 mm). Under the conditions of temperature 25°C, humidity 60RH, and atmospheric pressure 298.15K, quickly add 1 mL of electrolyte (DEC:EMC:DMC=1:1:1, hexafluorophosphate LIPF6, 1 mol / L) at the center of the circle, and observe and measure the radius of electrolyte diffusion after 1 minute.

[0125] 9. Air permeability value: using American Gurley4110N air permeability tester.

[0126] 10. Contact angle and dynamic contact angle: Use SINDIN contact angle tester to test the contact angle at 10s.

[0127] The porous alumina powders obtained in Examples 1 to 8 and the comparative samples obtained in Comparative Examples 1 to 5 were tested for particle size, pore volume, pore size, hydroxyl content, impurity content and infrared spectrum, and the test results are shown in Table 1.

[0128] Table 1

[0129]

[0130] It can be seen from Table 1 that the hydroxyl content on the porous alumina particles provided by the present application is lower, and the applicant performs infrared spectroscopy on the porous alumina particles prepared by the present application, and the test results are as follows: Figure 2 As shown in the figure, it can be seen that the porous alumina particles provided by the present application have a wave number of 1600 cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 100cm -1From the following infrared peaks, it can be seen that the porous alumina particles provided by the present application have a low affinity for water molecules, which is beneficial to the reliability optimization of the battery used therein. In addition, the repose angle of the porous alumina particles provided by the present application is controlled within the range of 38 to 45°, and the inventors found during coating that when the repose angle of the porous alumina particles provided by the present application is controlled within this range, the uniformity of the coating obtained by coating is good, and its heat shrinkage and strength (puncture strength, tensile strength) will also be improved, and the improvement is about 8% to 15% higher than that of the coating of spherical alumina.

[0131] The applicant has further studied the porous alumina provided in this application as ceramic particles for the diaphragm coating, and the coating has the characteristics of good thickness consistency, low surface protrusion rate, large injection volume, etc. Raw materials: porous alumina provided in Examples 1-8; porous alumina provided in Comparative Examples 1-5;

[0132] Conventional alumina powder, D50=0.4um, D50=0.8um, Suzhou Jinyi New Materials.

[0133] PE separator 9μm, Suzhou Jie Li New Energy Materials Co., Ltd.

[0134] Dispersant SF8, Japan Sannopco.

[0135] Adhesive BM900-B, Japan Zeon.

[0136] Polyoxyethylene lauryl ether, Nantong Haian Chemical.

[0137] Preparation of diaphragm samples:

[0138] Take 100g of alumina powder and 180g of deionized water respectively, stir and mix for 10min. Add 3g of dispersant SF8 and stir for 10min. Add 1.75g ​​of emulsifier lauryl alcohol polyoxyethylene ether and stir for 10min. Finally, add 5g of acrylic emulsion BM900-B and continue stirring for 30min to obtain ceramic slurry. Apply the ceramic slurry to the surface of PE diaphragm on the online rod coater, place it in a blast oven at 40℃ and dry it for 10min to obtain the coated diaphragm and perform performance testing. The test results are as follows.

[0139] Table 2

[0140]

[0141] As can be seen from Table 2, the electrolyte diffusion radius of the diaphragm coating formed by the porous alumina provided in the present application is significantly improved. When the substrate is consistent, the electrolyte diffusion radius is increased from the existing 13-15 mm to more than 22 mm. It can be seen that the alumina particles with specific morphology, particle size range and porous structure provided in the present application are conducive to the optimization of the electrolyte diffusion radius. In addition, the coating formed by the alumina provided in the present application also has a relatively obvious optimization of the air permeability value of the diaphragm.

[0142] The dynamic contact angles of electrolyte of the diaphragm coating formed by the porous alumina obtained in Example 1 and Comparative Examples 1 to 5 are shown in Table 3.

[0143] Table 3

[0144]

[0145] In addition, the applicant also tested the dynamic electrolyte contact angle and static electrolyte contact angle of the coating formed by the alumina provided in Example 1 and Comparative Examples 1 to 5 and conventional alumina, and the test results are shown in Table 3. It can be seen from the table that although the static electrolyte contact angle (50s) of the coating formed by the porous alumina obtained in the embodiment and the comparative example is not much different, there is a significant difference in the change of the dynamic contact angle, and the dynamic contact angle of the porous alumina decreases more rapidly, which can achieve rapid absorption of the electrolyte; and the porous alumina provided in the present application is not only particularly fast in the dynamic contact angle change curve, but also has a lower static contact angle, which may also be one of the reasons for the better electrolyte diffusion radius.

[0146] In addition, according to the above-mentioned preparation method of the diaphragm, the porous alumina obtained in Example 1 and the conventional alumina were respectively prepared into diaphragms with a coating thickness of 2 μm and 3 μm according to the coating thickness, and the liquid absorption rate, thickness uniformity of the coating, and surface convexity were tested. The test method and test results are as follows.

[0147] test

[0148] 1. Liquid absorption rate

[0149] The membranes with coating thickness of 2 μm and 3 μm respectively formed by the porous alumina coating obtained in Example 1 (Example 1 and Example 2 respectively) and the membranes with coating thickness of 2 μm and 3 μm respectively formed by the porous alumina coating obtained in Comparative Example 1 (Comparative Example 1 and Comparative Example 2 respectively) were cut into several rectangles of 20 mm×50 mm, recorded as AT1, AT2... and AL1, AL2..., and weighed respectively to obtain the membrane mass M1;

[0150] The diaphragm is completely immersed in the electrolyte and left for a period of time to ensure that the electrolyte is completely absorbed, and then the coated diaphragm is dried in the shade for 12 to 24 hours; the diaphragm after drying in the shade is weighed to obtain the mass of the diaphragm after soaking M2; the liquid absorption rate of multiple coated diaphragms is calculated, and the average value is taken as the final liquid absorption rate of the coated diaphragm: (M2-M1) / (M1*ρelectrolyte).

[0151] 2. Thickness uniformity

[0152] For a 20X50cm coated film, 3 points are tested at the front, middle and back, for a total of 6 points. The square root of the sum of the squares of the difference between the data points and the mean point is counted and calculated. The smaller the δ value, the higher the uniformity of the film thickness. The specific formula is as follows:

[0153] δ =

[0154] 3. Test of the number of protrusions on the membrane surface

[0155] A 20×50 cm coated film was placed under light, and the number of black spots was observed from the back and counted.

[0156] The test results are shown in Table 4.

[0157] Table 4

[0158]

[0159] From Table 4, we can see that the smaller the δ value, the better the thickness uniformity; the fewer the number of protrusions on the membrane surface, the smoother the ceramic diaphragm; the higher the liquid absorption rate, the better the performance. Porous alumina is used for diaphragm coating compared to conventional alumina. The diaphragm coating of porous alumina has the characteristics of good thickness consistency, low surface protrusion rate, and large liquid injection volume.

[0160] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A porous alumina powder for lithium ion batteries, characterized in that: The particle size D50 of the porous alumina powder is 0.3-2 μm; the specific surface area of ​​the porous alumina powder is 5-50 m 2 / g; the porous alumina powder includes at least 90% alumina particles with a quadrangular prism structure, and the amount of alumina particles with a spherical structure is no more than 0.5%, and the amount of alumina particles with a needle-shaped structure and a flaky structure is no more than 2%; The ratio of the edge length to the diagonal length of the bottom surface of the alumina particles with a tetrahedral prism structure is 1: (0.5~5); The surface hydroxyl content of the porous alumina powder is 5 / nm 2 Below, and its infrared spectrum at wave number 1600cm -1 ~3700cm -1 There is no area that exceeds its baseline and has a width of 100cm -1 The following infrared peaks; the particles in the porous alumina powder include a plurality of pores, the pore diameter of the pores is 5-50nm, and the pore volume is 0.01-0.4cm 3 / g.

2. The porous alumina powder for lithium ion batteries according to claim 1, characterized in that: The content of α-alumina in the porous alumina powder is not higher than 50%.

3. The porous alumina powder for lithium ion batteries according to claim 1, characterized in that: The pore diameter is 8-20 nm and the pore volume is 0.05-0.2 cm 3 / g; the specific surface area of ​​the porous alumina powder is 6~20m 2 / g.

4. The porous alumina powder for lithium ion batteries according to claim 1, characterized in that: The particles in the porous alumina powder are at least one of the θ phase, the δ phase, and the γ phase, or at least one of the η phase, the κ phase, the χ phase, and the ρ phase.

5. The porous alumina powder for lithium ion batteries according to claim 1, characterized in that: The porous alumina powder is directly prepared without compounding a variety of porous alumina powders.

6. A battery separator, characterized in that: The battery separator comprises a base film and a ceramic coating formed on at least one side of the base film, wherein the ceramic coating comprises the porous alumina powder according to any one of claims 1 to 5; and the base film is a polymer base film.

7. The battery separator according to claim 6, characterized in that: The liquid absorption performance of the battery separator is not less than 0.6 mL / g; the electrolyte diffusion radius of the battery separator is not less than 20 mm, wherein the electrolyte ratio is: DEC:EMC:DMC=1:1:1, hexafluorophosphate LIPF6, 1 mol / L.

8. A battery, characterized in that: The battery separator according to claim 7 is included.

9. An electrical device, characterized in that: Comprising the battery as claimed in claim 8.

Citation Information

Patent Citations

  • Lithium-ion battery diaphragm and preparation method thereof

    CN106784529A

  • Gamma-aluminum oxide octahedral particle with high specific surface area and preparation method of gamma-aluminum oxide octahedral particle

    CN112978771A